2013
DOI: 10.1016/j.compstruct.2012.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Shape memory polyurethanes reinforced with carbon nanotubes

Abstract: New shape-memory materials (SMMs) for applications in active control and morphing structures have been attracting special attention due to its unique properties. These SMM can be metallic alloys (SMAs), piezoelectric, and polymers such as polyurethanes (SMPUs). The latter detain higher recovery rates but better processability, however, the reaction time is longer when compared with the SMA. The addition of carbon nanotubes (CNTs) to SMPU seems to improve its overall properties with a great deal of potential in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…11(b) that there were two main peaks. The weight loss in the first peak can be related with the degradation of PCL segments while the second can be due to degradation of PEG segments [11,32]. As it can be seen, at T7-OH contents of 10 wt.% the stability of the materials was significantly affected by the presence of T7-OH, showing maximum degradation temperatures around 400°C.…”
Section: Thermal Degradation and In Vitro Degradation Researchmentioning
confidence: 88%
“…11(b) that there were two main peaks. The weight loss in the first peak can be related with the degradation of PCL segments while the second can be due to degradation of PEG segments [11,32]. As it can be seen, at T7-OH contents of 10 wt.% the stability of the materials was significantly affected by the presence of T7-OH, showing maximum degradation temperatures around 400°C.…”
Section: Thermal Degradation and In Vitro Degradation Researchmentioning
confidence: 88%
“…In that study, the authors demonstrated significant increases in the glass transition temperature (T g ) and degradation temperature (T d ), which moved from À25 C to À16 C and from 307.5 C to 360 C, respectively, with only a 0.5 wt% loading of CNTs [27]. This improvement in mechanical properties was also demonstrated by a significantly more rapid recovery when heated past T g (Fig.…”
Section: Smp-organic Compositesmentioning
confidence: 90%
“…The CNTs-filled polyurethane composites fabricated either via melt mixing, dispersion of CNTs in the solvent, and the dissolution of the polyurethane in the same solvent, followed by solvent evaporation or the reaction of the monomers or pre-polyurethane in the presence of dispersed CNTs (Gupta et al 2013;Liu et al 2013a, b, c). The former has not been tried; most probably due to weakly melting material has less tendency to disperse CNTs, since the latter technique is only industrially practical (Fonseca et al 2013;Zheng et al 2013). The latter technique accustomed to generate MWCNTs-filled polyurethane composites.…”
Section: Cnts: In Polyurethane Polymeric Compositesmentioning
confidence: 99%